Learning strategies of productive lesson at vocational high school in Serang City - Mohammad Fatkhurrokhman; Suroso Mukti Leksono; Sulaeman Deni Ramdan; Ikman Nur Rahman (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The purpose of this research are: (1) to know the design of delivery strategy of learning of productive lesson; (2) to know the implementation of delivery strategy of learning of productive lesson; and (3) to find out the result of applying the delivery strategy of learning of productive lesson. This research uses qualitative phenomenological approach with multi-case design. Informants in this study are students, teachers, leaders of Vocational High School in Serang City. Data collection through interviews and observation. Data analysis technique is Miles & Huberman interactive model. The results of this study found that (1) The design of the delivery of learning strategies productive lesson conducted by teachers is to design learning strategies by involving the media and based on the goal; (2) At the time of learning activities of productive lesson take place, the strategy used by teachers is the use of instructional media by demonstrating to students in front of the classroom; and (3) The implementation of learning delivery strategy of productive lesson applied by the teachers from each of the research sites resulted in increased value.